Asian courts in context / edited by Jiunn-rong Yeh and Wen-Chen Chang. - Ye, Junrong, 1958-; Chang, Wen-Chen (Law teacher) (Cambridge University Press, 2015)
The rise of Asia in global political and economic developments has been facilitated in part by a profound transformation of Asian courts. This book provides the most up-to-date and comprehensive analysis of these courts, explaining how their structures differ from courts in the West and how they have been shaped by the current challenges facing Asia. Contributors from across the continent analyze fourteen selected Asian jurisdictions representing varying degrees of development: Japan, Korea, Taiwan, India, Indonesia, Mongolia, the Philippines, Hong Kong, Singapore, Bangladesh, Malaysia, Thailand, China and Vietnam. Setting the courts of each region in the context of their country's economic, political, and social dynamics, this book shows how and why Asian courts have undergone such profound transformations in recent years and predicts the future trajectories of tradition, transition and globalization to suggest the challenges and developments that lie ahead.